PERUBAHAN STRUKTUR PEREKONOMIAN SEKTOR PERKEBUNAN INDONESIA1995-2000 : PENDEKATAN ANALISIS DEKOMPOSISI STRUKTUR (STRUCTURAL DECOMPOSITION ANALYSIS) - Mohammad Rondhi (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2015)
Indonesia has experienced steady economic growth in 1980s-1990s, then faced devastating during 2000s. The cricis affected to economic structure. However explanation of the effect especially to estate crops has not clear. This reserach is directed to respon these questions (1) how has the estate sector changed?, and (2) what are source of economic growth of the sectors?. We use Input-output table 1995 and 2000 form Statictic Indonesia to response these questions.Based on tha analysis we find that the economic cricis affect to lower ranking in backward linkage but has higher ranking in forward linkage for estate crops. In another side, the manufactur of estate sector has higher ranking for backward linkage but lower ranking for forward linkage. Then, there is increasing of output during economic cricis for estate sector (includes estate crops and its manufacture). The source of the increasing are final domestic demand and export rather than technological change. This research suggest that to improve the estate crops buy improving the technology.Keywords: estate sectors, backward and forward linkages, structural decompocition analysis